2019
DOI: 10.1002/berj.3576
|View full text |Cite
|
Sign up to set email alerts
|

Educational engagement, expectation and attainment of children with disabilities: Evidence from the Scottish Longitudinal Study

Abstract: Government statistics show that children with special educational needs and disabilities do not achieve as well academically as their peers, which impacts on later employment and socioeconomic circumstances. Addressing these inequalities is a key policy area which currently lacks a satisfactory evidence base. To explore the issue, the present study used data from the Scottish Longitudinal Study which contains data from the 1991, 2001 and 2011 censuses along with other administrative data, from a representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In comparison to their peers, children and young people with disability face significant inequities. This group is more likely to experience poorer health outcomes, be excluded or suspended from school and less likely to be employed (Cox & Marshall, 2020; Hall, Fildes, Liyanarachchi, Plummer, & Reynolds, 2019). Evidence from previous pandemics suggests that these events worsen inequities (Quinn & Kumar, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to their peers, children and young people with disability face significant inequities. This group is more likely to experience poorer health outcomes, be excluded or suspended from school and less likely to be employed (Cox & Marshall, 2020; Hall, Fildes, Liyanarachchi, Plummer, & Reynolds, 2019). Evidence from previous pandemics suggests that these events worsen inequities (Quinn & Kumar, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Special mention must be made of students with disabilities, since several of the analysed studies [ 27 , 51 , 59 , 62 ] showed that, in a pandemic situation and compared to fellow pupils, these groups are at a disadvantage in terms of education and well-being. This is not a new finding since, in previous studies, this group’s educational, social, and employment differences have been highlighted [ 88 ].…”
Section: Discussionmentioning
confidence: 65%
“…The term special educational needs (SEN) is applicable in both cases and embraces students at risk of failing to achieve educational goals for a wide variety of reasons (United Nations Educational, Scientific and Cultural Organization [UNESCO], 1994), making them eligible for additional or different educational services and support to meet their learning needs in school (European Agency for Special Needs and Inclusive Education [European Agency], 2020). Students with SEN show poorer academic achievement in upper secondary school (Cox & Marshall, 2020;Hakkarainen, Holopainen & Savolainen, 2013;Yoder & Cantrell, 2019), higher levels of school absence (Attwood & Croll, 2015;Havik, Bru & Ertesvåg, 2015) and a greater drop-out rate (Hakkarainen et al, 2015;Korhonen, Linnanmäki, & Aunio, 2014;Yoder & Cantrell, 2019) than students without SEN. Furthermore, they are less likely to graduate from upper secondary school (Yoder & Cantrell, 2019).…”
Section: Students With Special Educational Needs (Sen)mentioning
confidence: 99%